Strategi Tabligh berbasis Kebudayaan Sunda - Fakhruroji, Moch. (UIN Sunan Gunung Djati Bandung, 2009)
principle which can not be ignored in the practice of tabligh as dakwah activities is the importance of local wisdoms. This is related to effectiveness tabligh practices, because tradition or customs is a value system which has some connections among people, in this case,Sundanese community. Thereby, tabligh as an orthogonal transformation process of Islamic values has importance in dealing with Sundanese cultures. One of the strongest dimension cultures is language. In so many things, Sundanese language becomes a determinant channel in almost every tabligh activit ies in Sundanese community, particularly Sundanese community is relatively closed to Islamic values. The using of Sundanese language in tabligh processes is a sophisticated effort to prove that a mubaligh believes that urf is one of the most important things to make some changes.